2017
DOI: 10.3390/app7060595
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Characteristics of X-, C- and L-Band PolSAR Data Examined for the Tundra Environment of the Tuktoyaktuk Peninsula, Canada

Abstract: Abstract:In this study, polarimetric Synthetic Aperture Radar (PolSAR) data at X-, C-and L-Bands, acquired by the satellites: TerraSAR-X (2011), Radarsat-2 (2011), ALOS (2010) and ALOS-2 (2016), were used to characterize the tundra land cover of a test site located close to the town of Tuktoyaktuk, NWT, Canada. Using available in situ ground data collected in 2010 and 2012, we investigate PolSAR scattering characteristics of common tundra land cover classes at X-, C-and L-Bands. Several decomposition features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…Fresh vegetation canopy can increase the fraction of volume scattering and positively affect backscatter intensity [27]. Existing studies on the effect of tundra vegetation on backscatter [23,32,56] do not address the effect of fresh vegetation on previously degraded tundra surfaces. The mixed signals of vegetated and eroding surfaces within the cliff AOIs could explain the higher standard deviations of backscatter in 2015.…”
Section: Backscatter Dynamics Of Tundra and Cliff Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fresh vegetation canopy can increase the fraction of volume scattering and positively affect backscatter intensity [27]. Existing studies on the effect of tundra vegetation on backscatter [23,32,56] do not address the effect of fresh vegetation on previously degraded tundra surfaces. The mixed signals of vegetated and eroding surfaces within the cliff AOIs could explain the higher standard deviations of backscatter in 2015.…”
Section: Backscatter Dynamics Of Tundra and Cliff Surfacesmentioning
confidence: 99%
“…Investigations from Widhalm et al [24], Antonova et al [27] and Ullmann et al [32] on X-Band SAR data in tundra landscapes showed low spatial variability in X-Band backscatter for different tundra types (polygonal wet tundra and shrub tundra) during the snow free summer months. In contrast, bare ground conditions that occur after erosion and are accompanied by the removal of the vegetation layer have been shown to have higher backscatter in X-Band with HH polarization [32].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…An additional valuable parameter for water classification would be water levels, which have successfully been determined from wetland in SAR [40]. Multi-frequency acquisitions from different satellites, in combination with Kennaugh element decomposition, has also shown great potential for discriminating different vegetation types (e.g., [41]).…”
Section: Discussionmentioning
confidence: 99%
“…O. Yuzugullu, E. Erten, and I. Hajnsek developed in a study [5] on the estimation of biophysical variables in rice fields by employing X-band copolar data and electromagnetic modeling of the scene. Also related to vegetation, but with a broader environmental scope, the paper coauthored by T. Ullmann, S. N. Banks, A. Schmitt, and T. Jagdhuber [6] describes the response of a large number of polarimetric observables, obtained at L-, C-, and X-bands in a tundra scene located in Canada. The use of shorter wavelength imagery (X and C) was beneficial for the characterization of wetland and tundra vegetation, while L-band data highlighted differences between the bare ground classes better.…”
Section: Polarimetric Sar: Techniques and Applicationsmentioning
confidence: 99%